Volumetric Analysis of Hepatocellular Carcinoma After Transarterial Chemoembolization and its Impact on Overall Survival - Hajkova, Monika; Andrasina, Tomas; Ovesna, Petra; Rohan, Tomas; Dostal, Marek; Valek, Vlastimil; Ostrizkova, Lenka; Tucek, Stepan; Sedo, Jiri; Kiss, Igor (In Vivo, 2022)
BACKGROUND/AIM: To evaluate the prognostic value of Response Evaluation Criteria In Solid Tumors (RECIST), modified RECIST and volumetric analysis in patients with hepatocellular carcinoma (HCC) treated by transarterial chemoembolization (TACE). PATIENTS AND METHODS: This single-center prospective cohort study included a total of 61 patients with HCC treated by transarterial chemoembolization (TACE). The response of TACE was evaluated on preprocedural and postprocedural CT by two radiologists using RECIST/mRECIST and volumetric response to treatment. Each response assessment method was used to classify the response as progressive disease, stable disease, partial response and complete response. Kaplan-Meier analysis with log-rank test was performed for each method to evaluate its ability to help predict overall survival and progression free survival. Interobserver variability and reproducibility was determined by the Pearson and Spearman correlation coefficients. RESULTS: The median overall survival was 17.1 months and the median progression-free survival was 11.1 months. Volumetric assessment was proved to be a prognostic factor for overall survival (p<0.01) and progression-free survival (p<0.001), contrasting with RECIST and mRECIST. All three methods featured very small interobserver variability (p<0.001 for Pearson and Spearman correlation coefficients). The patients classified as having stable disease had a 3.8-fold higher risk of death than the patients classified as having a complete/partial response (HR=3.82; 95% Confidence Interval (CI)=1.32-11.02; p=0.013) and a 4.5-fold higher risk of progression (HR=4.46; 95% CI=1.72-11.61; p=0.002). CONCLUSION: The prognostic value of volumetric analysis in patients with HCC treated by TACE appears to be superior to RECIST and mRECIST, with a real impact in everyday practice.
Keywords: Reproducibility of Results; lidé; chemoembolizace; nádory jater; reprodukovatelnost výsledků; prospektivní studie; Carcinoma, Hepatocellular; Liver Neoplasms; Prospective Studies; hepatocelulární karcinom; Chemoembolization, Therapeutic; Humans